Simulation of Industrial Crystal Growth by the Vertical Bridgman Method - Boschert, Stefan; Schmidt, Alfred; Siebert, Kunibert G.; Bänsch, Eberhard; Benz, Klaus-Werner; Dziuk, Gerhard; Kaiser, Thomas (Mathematics - Key Technology for the Future, 2003)
Single crystals of Cadmium-Zinc-Telluride are used as a substrate material for the production of infrared detectors and are usually grown by the vertical Bridgman method. We present a simulation of the whole growth process in two steps: In the first step, the (stationary) heat transport in the furnace is modeled and calculated for different positions of the ampoule. This provides information about the most important parameter during this process: the temperature distribution in furnace and ampoule. The obtained temperatures are then used in the second step as boundary conditions for the (time dependent) simulation of temperature and convection in the ampoule. Only the use of adaptive finite element methods allows an efficient numerical simulation of the moving phase boundary, the convection in the melt and the temperature distribution in melt and crystal. Numerical results are presented for both furnace and ampoule simulations.
UnivIS-Import:2015-04-20:Pub.2003.nat.dma.lama3.simula